Der Ausdruck der Modalität der Verallgemeinerung im Deutschen und Polnischen - Ölender, Maria (Studia Germanica Posnaniensia, 2018)
The article takes up the problem of modality and is especially an attempt at establishing equivalences between German and Polish. On the basis of unilateral and selective method of confrontation the author analyses the relevant modality particles and establishes equivalents on the Polish side. Conclusions are concerned with inter-linguistic differences and similarities in the scope investigated by the author.